Topside Ionospheric Disturbances Detected Using Radio Occultation Measurements During the August 2017 Solar Eclipse. Issue 13 (1st July 2019) - Perry, G. W.; Watson, C.; Howarth, A. D.; Themens, D. R.; Foss, V.; Langley, R. B.; Yau, A. W.
Abstract: The CASSIOPE (also known as Swarm‐E) satellite crossed the path of totality of the August 2017 eclipse at 640‐km altitude 10 min following the lunar umbra. Observations from CASSIOPE's Global Positioning System radio occultation receiver reveal total electron content variations of 0.2–0.3 total electron content units in the topside ionosphere—a signature of medium‐scale (100‐200 km) plasma disturbances in the lunar penumbra that were induced by the eclipse. The variations were only observed during the eclipse, their absence on preceding days being consistent with their very low (<10%) statistical occurrence probability. Their spectral characteristics match those of other contemporaneous measurements, and their detection is consistent with the simulated ionosphere‐thermosphere response to the eclipse. To capture the small‐scale size of the variations or to simulate those expected in the upcoming (July 2019) total eclipse, ionosphere‐thermosphere model runs with a spatial resolution of 50 km or better would be required. Plain Language Summary: During the August 2017 "Great American Eclipse, " the Global Positioning System‐receiver‐based instrument on board the CASSIOPE (also known as Swarm‐E) satellite detected significant disturbances in the terrestrial ionosphere at multiple distributed locations above the United States. Previous research on solar eclipses has pointed out the difficulty in linking such disturbances to an eclipse, given other known generation mechanisms, casting doubt on their possible linkage to the August 2017 eclipse. By virtue of the multiple locations of the measurements over the continental United States during the eclipse and the days preceding the eclipse, and the techniques used in the analysis, the data offer compelling evidence that the disturbances were directly generated by the eclipse. The measurements offer unique insight into how the Earth's upper atmosphere and ionosphere respond to an impulsive event such as a solar eclipse. The detected disturbances have sizes of 100‐200 km. To capture their "medium" scale size in model simulations including those expected to be seen in the upcoming July 2019 eclipse, it will be necessary to run the existing ionosphere‐thermosphere models at high spatial resolution (50 km or better). Key Points: CASSIOPE GPS radio occultations reveal topside ionospheric disturbances induced by the August 2017 eclipse 0.2–0.3 TECU variations were observed; the presence is atypical for topside but consistent with modeling simulations and other measurements Scale of disturbances necessitates better spatially resolved simulations to model the ionosphere‐thermosphere response to a total eclipse